Comparative evaluation of influence of aging, soil properties and structural characteristics on bioaccessibility of polychlorinated biphenyls in soil. (November 2018) - Ti, Qingqing; Gu, Chenggang; Liu, Chang; Cai, Jun; Bian, Yongrong; Yang, Xinglun; Song, Yang; Wang, Fang; Sun, Cheng; Jiang, Xin
Abstract/Purpose: Though bioaccessibility commonly recognized as a guideline for risk assessment is closely related with pollution occurrence and chemical species of compounds, the mechanistic links are barely evaluated particularly for widespread polychlorinated biphenyls (PCBs) in soil. With the biomimetic extraction of hydroxypropyl-β-cyclodextrin (β-HPCD), the temporal and spatial influences of soil properties, aging and structural characteristics, e.g. polarity of PCB congeners on bioaccessibility were investigated for PCBs. Sensitive variation of bioaccessibility with aging, soil organic matter (SOM), particle size and soil moisture were clearly evidenced for different PCB congeners. Due to aging, the bioaccessibility decreased in the long term after stabilization for 36 h. In concert with the first-order kinetics, the decay rates of bioaccessibility were shown with congener-specificity and were well correlated with dipoles of PCBs. The increment of SOM diminished the bioaccessibility for the strengthened adsorption while the increased particle size and soil moisture elevated it possibly due to the less adsorption on soil particles and more accommodation of PCBs in soil pore water. Except the positive correlations with particle size, soil moisture and dipole moment, the greater dependency on aging and SOM was highlighted for bioaccessibility by partial least squares (PLS) analysis. The mutual relationship with influential factors was quantitatively formulated for accelerative prediction of bioaccessibility, and the comparative evaluation and detailed insights into the mechanistic links would thus help enhance the precise determination of bioaccessibility and risk assessment of PCBs in soil. Highlights: Bioaccessibility was susceptible to aging, soil properties and congener specificity. Bioaccessibility decayed in first-order kinetics with aging after stabilization. Larger soil particle size, soil moisture and PCBs polarity improved bioaccessibility. Greater dependency on aging and SOM was highlighted for bioaccessibility by PLS. Mechanistic links were shown with formulated relationship for PCBs bioaccessibility.